Young Children’s Representation of Locations in a Series: A Front-Back Representation or an Ordinal Representation? - Hu, Qingfen; Fu, Yuejia; Shao, Yi (Frontiers in Psychology, 2020)
Previous research has found that 3- to 5-year-old children could encode and retrieve a target location in a two-location series. In a paradigm of running two symmetrical railcars on a circular track, the study suggested that children used front-back array to help coding. That is, children at this age code the railcar running in the front of another as “the location in the front” and the railcar running in the back of another as “the location in the back”. However, the children’s success could be attributed to an alternative interpretation: using an ordinal representation to encode the location in front as the first with the other as the second. The current study used a four-location series to examine children’s mental representation. Three- to 5-year-old children participated in a hide-and-seek game to remember a target location out of four locations that moved in a series. The results showed salient individual differences in children’s representation, and their performance improved as the representation progressed. An ordinal representation supported the precise encoding of each location, while a vague front-back representation and a clearer front-middle-back representation led to different performance.